Lateralized Cerebellar Contributions to Word Generation: A Phonemic and Semantic Fluency Study - Tom A. Schweizer; Michael P. Alexander; B. A. Susan Gillingham; Michael Cusimano; Donald T. Stuss (Behavioural Neurology)
Impairment on verbal fluency tasks has been one of the more consistently reported neuropsychological findings after cerebellar lesions, but it has not been uniformly observed and the possible underlying cognitive basis has not been investigated. We tested twenty-two patients with chronic, unilateral cerebellar lesions (12 Left, 10 Right) and thirty controls on phonemic and semantic fluency tasks. We measured total words produced, words produced in the initial 15 seconds, errors and strategy switches. In the phonemic fluency task, the right cerebellar lesion (RC) group produced significantly fewer words compared to the left cerebellar lesion (LC) group and healthy controls, particularly over the first 15 seconds of the task with no increase in errors and significantly fewer switches over the entire task. In the semantic fluency task there was only a modest decrease in total words in the RC group compared to controls. RC lesions impair fluency with many of the same performance characteristics as left prefrontal lesions. This supports the hypotheses of a prefrontal-lateral cerebellar system for modulation of attention/executive or strategy demanding tasks.